DAMPAK STEVIOL GLIKOSIDA PADA GLUKOSA DARAH PUASA: WAWASAN DARI TINJAUAN LITERATUR KOMPREHENSIF - Gusnawati, Gusnawati; M. Hutapea, Albert (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The natural sweetener from Stevia rebaudiana Bertoni, steviol glycoside (SG), has been proposed to exhibit various antidiabetic properties. This low-calorie artificial sweetener is claimed to be a safe sweetener and is recommended for use by diabetes sufferers because it does not affect the patient's blood glucose levels after consumption. The aim of this literature-based review is to synthesize the available scientific information regarding steviol glycosides as natural sweeteners and molecules with therapeutic potential. Additionally, it also addresses safety issues related to human consumption. Steviol glycosides exhibit superior sweetening properties compared to sucrose and are noncaloric, noncariogenic, and nonfermentative. Method: data sources from journals were obtained through electronic database searches in PubMed, ResearchGate, Google Scholar, EMBASE and full text bibliography. Conclusion Evidence from published RCTs shows that Steviol glycosides can reduce blood pressure and fasting blood sugar. The magnitude of the impact is small, and large heterogeneity limits the strength of any impact. Keywords: Stevia; Effect, Steviol glycoside; Type 2 diabetes; Blood sugar.